2013
DOI: 10.1016/j.molmet.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The human lipodystrophy protein seipin is an ER membrane adaptor for the adipogenic PA phosphatase lipin 1

Abstract: Disruption of the gene BSCL2 causes a severe, generalised lipodystrophy, demonstrating the critical role of its protein product, seipin, in human adipose tissue development. Seipin is essential for adipocyte differentiation, whilst the study of seipin in non-adipose cells has suggested a role in lipid droplet formation. However, its precise molecular function remains poorly understood. Here we demonstrate that seipin can inducibly bind lipin 1, a phosphatidic acid (PA) phosphatase important for lipid synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 41 publications
4
95
2
1
Order By: Relevance
“…We have previously shown that within cells the lipins form tetramers (34), and by atomic force microscopy, we have found that recombinant lipin 1 can form even higher order structures on lipin bilayers (35). In addition, lipin 1 has been found to interact with the human lipodystrophy protein seipin (36), and seipin itself has been found to form large oligomeric structures (37)(38)(39). Although the identification of lipin localization to punctate spots is interesting, further study will be necessary to uncover the nature and/or function of lipin protein cellular localization to these structures.…”
Section: Discussionmentioning
confidence: 95%
“…We have previously shown that within cells the lipins form tetramers (34), and by atomic force microscopy, we have found that recombinant lipin 1 can form even higher order structures on lipin bilayers (35). In addition, lipin 1 has been found to interact with the human lipodystrophy protein seipin (36), and seipin itself has been found to form large oligomeric structures (37)(38)(39). Although the identification of lipin localization to punctate spots is interesting, further study will be necessary to uncover the nature and/or function of lipin protein cellular localization to these structures.…”
Section: Discussionmentioning
confidence: 95%
“…SEIPIN acts in ER-LD contact sites to enable nascent LDs to acquire more lipids from the ER and grow to form mature LDs [12,15]. SEIPIN also regulates the metabolism of phosphatidic acid (PA) at the LD-ER contact, acting as a scaffolding protein recruiting PA-metabolism enzymes such as LIPIN1 and AGPAT2 [16,17] as well as controlling PA levels by inhibiting GPAT [18]. In addition to being the biosynthetic precursor of phospholipids and TAGs, PA is a cone-shaped phospholipid that facilitates LD fusion [19,20] and could be accommodated in the regions of negative membrane curvature associated to LD budding and LD-ER connections [21].…”
Section: The Er In Ld Biogenesis and Growthmentioning
confidence: 99%
“…Pah1 is recruited to nuclear membrane foci in contact with LDs (23,58) and is required for LD biogenesis (22,23,62). Interestingly, in mammalian cells, it was observed that seipin interacts with lipin1, the human homolog of Pah1 (64). Thus, the seipin complex might function as a nucleation spot for NL biosynthetic enzymes.…”
Section: The Contribution Of Er-ld Contact Sites To Ld Formation and mentioning
confidence: 99%